2008
DOI: 10.1021/bi800515c
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminus of Apolipoprotein A-V Adopts a Helix Bundle Molecular Architecture

Abstract: Previous studies of recombinant full-length human apolipoprotein A-V (apoA-V) provided evidence of the presence of two independently folded structural domains. Computer-assisted sequence analysis and limited proteolysis studies identified an N-terminal fragment as a candidate for one of the domains. C-Terminal truncation variants in this size range, apoA-V(1-146) and apoA-V(1-169), were expressed in Escherichia coli and isolated. Unlike full-length apoA-V or apoA-V(1-169), apoA-V(1-146) was soluble in neutral-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…38 ) suggested a domain organization for lipid-free apoA-V analogous to that previously determined for apoA-I ( 39 ) and apoE ( 40 ). Thus, in the absence of lipids, apoA-V would be expected to feature an elongated, four-helix bundle comprising apoA-V interactions with sortilin covalently bound to CM5 sensor chips are shown in Fig.…”
Section: Apoa-v Stimulation Of Lpl Activitysupporting
confidence: 63%
See 1 more Smart Citation
“…38 ) suggested a domain organization for lipid-free apoA-V analogous to that previously determined for apoA-I ( 39 ) and apoE ( 40 ). Thus, in the absence of lipids, apoA-V would be expected to feature an elongated, four-helix bundle comprising apoA-V interactions with sortilin covalently bound to CM5 sensor chips are shown in Fig.…”
Section: Apoa-v Stimulation Of Lpl Activitysupporting
confidence: 63%
“…However, and to verify this point while avoiding protein aggregation, we subjected wild-type apoA-V to limited proteolysis with pepsin at acidic pH, similar to a recent report (see Materials and Methods and Ref. 38 ). As shown in supplementary Fig.…”
Section: Cloning Expression and Characterization Of Recombinant Hummentioning
confidence: 99%
“…Unlike the full-length protein, recombinant apoA-V(1-146) was soluble in neutral-pH buffer in the absence of lipid (26). Guanidine HCl denaturation experiments at pH 3.0 yielded a one-step native-to-unfolded transition that corresponds directly with the more stable component of the two-stage denaturation profile exhibited by full-length apoA-V. Taken together, the data suggest that the N-terminal 146 residues of human apoA-V adopt a helix bundle molecular architecture in the absence of lipid and thus likely exist as an independently folded structural domain within the context of the intact protein.…”
Section: Unique Aspects Of Apoa-v Structurementioning
confidence: 99%
“…This finding is consistent with the stability properties of these apolipoproteins. At physiological pH apoA-V(1-146) is less stable than apoE3 NT (guanidine HCl denaturation midpoint of 2.0 M versus 2.5 M, respectively) (8,36) yet is more stable than apoA-I (1 M guanidine HCl denaturation midpoint) (37). Thus, it appears that the intrinsic stability of helix bundle apolipoproteins in solution correlates directly with the ability to bind newly created sites on a spherical lipoprotein substrate (8).…”
Section: Apoa-v(mentioning
confidence: 99%
“…Structural studies revealed that apoA-V is a two-domain protein (7) and that its N-terminal 146 residues adopt a helix bundle structure in the absence of lipid (8). Truncated apoA-V proteins in this size range have been reported in human subjects with severe hypertriglyceridemia (HTG) (9,10).…”
mentioning
confidence: 99%